2002
DOI: 10.1095/biolreprod.102.007013
|View full text |Cite
|
Sign up to set email alerts
|

Spermadhesin PSP-I/PSP-II Heterodimer and Its Isolated Subunits Induced Neutrophil Migration into the Peritoneal Cavity of Rats1

Abstract: Spermadhesins are a group of (glyco)proteins from seminal fluid involved in various aspects of porcine fertilization. PSP-I/PSP-II, a heterodimer of glycosylated spermadhesins, is the major component of porcine seminal fluid. Its biological function remains, however, enigmatic. Using an in vitro chemotaxis assay, we showed that PSP-I/PSP-II and its isolated subunits induced migration of purified neutrophils. A possible proinflammatory activity of PSP-I/PSP-II induced upon injection of the spermadhesin heterodi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 19 publications
0
21
0
1
Order By: Relevance
“…PSP-I and AWN-1 are members of the spermadhesin protein family isolated from seminal plasma and may play an important role during fertilization (Tö pferPetersen et al, 1998;Yang et al, 1998;ManĂĄ skovĂĄ et al, 2000;Assreuy et al, 2002). PSP-I has multiple forms because of differences in its carbohydrate moiety (Rutherfurd et al, 1992;Nimtz et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PSP-I and AWN-1 are members of the spermadhesin protein family isolated from seminal plasma and may play an important role during fertilization (Tö pferPetersen et al, 1998;Yang et al, 1998;ManĂĄ skovĂĄ et al, 2000;Assreuy et al, 2002). PSP-I has multiple forms because of differences in its carbohydrate moiety (Rutherfurd et al, 1992;Nimtz et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…The major seminal plasma glycoprotein (PSP-I), isolated and identified from boar seminal plasma by Rutherfurd et al (1992), may prevent premature capacitation and the acrosome reaction (Kwok et al, 1993;Tö pfer-Petersen et al, 1998). This protein may also have immunoregulatory activity (Kwok et al, 1993;Yang et al, 1998;Assreuy et al, 2002Assreuy et al, , 2003. AWN-1 is another spermadhesin that affects zona pellucida-binding activity (Sanz et al, 1992;RodrĂ­guez-MartĂ­nez et al, 1998) and may also have a role in the capacitation process (Calvete et al, 1997;Tö pfer-Petersen et al, 1998).…”
mentioning
confidence: 99%
“…Hence, PSP‐I and PSP‐II are immunostimulatory for lymphocyte activity in vitro (Nimtz et al, 1999), and binding of PSP‐I to lymphocyte has been demonstrated (Yang et al, 1998). Furthermore, the PSP‐I/PSP‐II heterodimer and its isolated subunits induce the recruitment of neutrophils into the peritoneal cavity of rats (Assreuy et al, 2002) and pigs (RodrĂ­guez‐MartĂ­nez et al, 2005). The neutrophil migration‐inducing activity of PSP‐I/PSP‐II, and possibly of the PSP‐II subunit, is mediated by the stimulation of resident macrophages, which release a neutrophil chemotactic substance (Assreuy et al, 2002), whereas PSP‐I appears to act directly on neutrophils (Assreuy et al, 2003).…”
mentioning
confidence: 99%
“…Therefore, they have been implicated in the carbohydrate-mediated events during sperm transport through the female reproductive tract and fertilization e.g. immunosuppression (PSP-I/PSP-II complex; Nimtz et al, 1999;Assreuy et al, 2002), spermoviduct interaction (AQN-1; Wagner et al, 2002;EkhlasiHundrieser et al, in press), and gamete interaction (Rodriguez-Martinez et al, 1998). The flexible glycan chains presented by the epithelial cells and the zona pellucida may anchor the entering sperm to the oviductal epithelium and the capacitating sperm to the gamete allowing then all down stream events.…”
Section: Molecular Variation and Functionmentioning
confidence: 99%